Evaluation of laser heterodyne radiometry for numerical weather prediction applications. (2nd October 2018) - Smith, Fiona; Havemann, Stephan; Hoffmann, Alex; Bell, William; Weidmann, Damien; Newman, Stuart
Abstract : This article reports the results of a preliminary mission study to assess the potential of space‐borne laser heterodyne radiometry (LHR) for the remote sensing of temperature for assimilation in a numerical weather prediction (NWP) model. The LHR instruments are low cost and small in size, lending themselves to a wide variety of satellite platforms. The impact of different configurations of an idealized LHR instrument is assessed against the Infrared Atmospheric Sounding Interferometer (IASI), via single‐column linear information content analysis, using inputs consistent with the background errors of the Met Office 4D‐Var assimilation system. Multiplexed configurations give promising results, in particular for sounding of upper‐atmospheric temperatures. Abstract : A preliminary mission study on the potential of space‐borne laser heterodyne spectro‐radiometers for temperature sounding is carried out using micro‐spectral window analysis of carbon dioxide absorption/emission. The main metric used for assessment is the retrieval information content and Degree of Freedom for Signal (DFS). In this picture, the evolution of the DFS across a micro‐spectral window is shown, characterizing the molecular transitions most contributing to the information retrieved.